Perancangan Sistem Informasi Pelayanan Masyarakat Berbasis Web untuk Meningkatkan Efisiensi dan Transparansi di Kantor Desa Teluk Dalem - Putri Amelinda; Emir Fajar Saputra; Suyitno Adi Purnomo (Jurnal Cendikia, 2025)
The development of information technology encourages digital transformation in various sectors, including public services at the village level. Village governments, as basic service providers for the community, are required to provide fast, efficient, and transparent services. However, many villages still rely on manual administrative processes, including Teluk Dalem Village, Mataram Baru Sub-district, East Lampung Regency. This research aims to design and implement a web-based community service information system to improve the quality of village public services. The method used was Research and Development (R&D) with a prototyping approach. Data collection techniques were conducted through observation, interviews, and literature studies. The developed system includes administrative document submission services such as KTP, Family Card, Birth Certificate, SKTM, and Death Letter. The implementation results show an increase in service efficiency, queue reduction, and increased transparency and accountability of the service process. This system also supports the achievement of the smart village concept through digitization of services that are responsive to community needs. This research is expected to become a model for developing village information systems that can be replicated in other areas.